Association of Long Non-Coding RNA Malat1 with Serum Levels of Interleukin-1 Beta and Vitamin D in Patients with Ischemic Stroke: - Borhani-Haghighi, Afshin; Bayat, Mahnaz; Tabrizi, Reza; Salehi, Mohammad Saied; Karimi, Najmeh; Rahimi, Moosa; Hooshmandi, Etrat; Razavi moosavi, Niloufar; Fadakar, Nima (Galen Medical Journal, 2023)
Background:Previous studies have demonstrated the strong association of inflammatory cytokines and vitamin D (VitD) deficiency and ischemic stroke (IS) pathogenesis. Due to the negative correlation between long non-coding RNA (lncRNA) Malat1 and pro-inflammatory factors we decided to investigate the associations between Malat1 expression with serum interleukin-1β (IL-1β), and VitD levels in IS patients. Materials and Methods:In this cross-sectional study, 63 IS patients were included. We used enzyme-linked immunosorbent assays to evaluate the serum levels of VitD and IL-1β. Malat1 expression was evaluated by the real-time polymerase chain reaction test. The associations between Malat1expression with VitD and IL-1β were analysed with linear regression (Stepwise model) and Pearson’s correlation analysis. Results: The Malat1 expression was inversely correlated with stroke severity (r=-0.25, P=0.043). Stepwise regression analysis showed a significant positive relationship between VitD level and Malat1 expression (Beta=0.28, P=0.02), and also showed a non-significant negative relationship between IL-1β and stroke severity. VitD level showed a positive Pearson correlation with Malat1 (r=0.28, P=0.023) and a negative correlation with IL-1β (r=-0.29, P=0.018) while it could not detect a significantly negative correlation with stroke severity. Conclusion: For the first time the associations between Malat1 expression with IL-1β and VitD in IS patients was analyzed. We found a significant positive relationship between VitD and Malat1. This correlation needs to be investigated with a larger sample size to achieve a strong and reliable association between VitD and Malat1.[GMJ.2023;12:e2457]